Purposive Communication Through Pecha Kucha Teaching and Learning: A Phenomenological Approach - Leovigildo Lito Mallillin (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2026)
The study aims to identify the Pecha Kucha in Purposive Communication subject in teaching and learning process.Qualitative phenomenological approach is utilized in the process of research design where it measures the contribution of Purposive Communication through Pecha Kucha in teaching and learning. The study comprised One Hundred Fifty (150) respondents only. Results show that improve communication skills are focused on enhancing speaking and confidence in the oral presentation where it develops speaking capacity and skills concise communication process ability, show that expand vocabulary is focused on specific language for Pecha Kucha vocabulary and knowledge process where it enhances the approach in the language proficiency engagement interesting and dynamic vocabulary knowledge, show that improve organization provides clear structure on the main ideas in outlining the logical progress of the message and conclusions where it visualizes the process of communication to ensure the topic to direct discussion in teaching and learning, and show that reinforce language concepts emphasize utilization to encourage teaching and learning on relevant connectors of vocabularies where it provides structure and feedback, correct word utilization, fluency, and pronunciation of the language concept and presentation.